Violation Of Cooperation Principles To Build Humor In Bu Gin's Tiktok And Its Relevance To Indonesian Anecdote Text Learning - Yunita Alifia Atmawati; Yunus Sulistyono (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2025)
Violations of the principle of cooperation often occur in TikTok video uploads. One of them is on the tiktok account @Bu Gin's. This research focuses on the violation of the principle of cooperation in the tiktok account @Bu Gin's and the emergence of humor which is motivated by the violation of the principle of cooperation. The method used in this research is a qualitative descriptive research method. The data in this research are fragments of conversations contained in video uploads on the TikTok account @Bu Gin's which are suspected to contain maxims that violate the principle of cooperation. The data collection method and technique in this research is by using listening and taking notes. Violations of the principles of cooperation include the maxim of quantity, maxim of quality, maxim of relevance, and maxim of implementation/method. From the data obtained, the occurrence of the maxim of quantity was most frequently found.